The Effect of Student Teams Achievement Divisions (STAD) Model and Standard Language Mastery on Students' Argument Writing Skills - Setiawati, Ni Wayan (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
This research aims to find out: (1) Differences in writing skills between students who study using the Student Team’s Achievement Divisions (STAD) and students who study using conventional approach. (2) The difference in argumentative writing skills between students who use the Student Teams Achievement Divisions (STAD) and those who learn through conventional approach. (3) The difference in writing skills between students with limited command of the standard language who study using the Student Teams Achievement Divisions (STAD) and students who learn using the conventional approach. (4) The interaction between the student teams achievement divisions (STAD) model and mastery of standard language on argumentative writing skills. This study uses quantitative research with experimental methods. Data collection techniques using tests. The data collected was processed using two-way analysis of variance (ANAVA) with the SPSS. The result of this research showed that (1) there is a significant effect between the implementation of STAD's on students' argumentative writing skills. This is indicated by the F value of 8.376 at a significant level of 0.05. (2) There is a significant effect between mastery of standard language on students' argumentative writing skills. (3) There is a significant effect between the implementation of the STAD model and mastery of standard language on students' argumentative writing skills. (4) There is no interaction between the student team’s achievement divisions (STAD) model and mastery of standard language on students' argumentative writing skills, this is indicated by a significant value of 0.710 in the interaction of the learning model and standard language mastery, which is greater than 0.05, indicating that H0 is accepted.